1985
DOI: 10.1161/01.str.16.2.285
|View full text |Cite
|
Sign up to set email alerts
|

A histochemical study of cerebral cortical vessels and ganglionic vessels of the caudatoputamen in aging normotensive rats.

Abstract: SUMMARYThe goal was to describe the metabolic profile of ganglionic and cortical arteries and arterioles in aging normotensive male rats. Five enzymes indicative of key metabolic pathways in the vessel walls were semiquantitatively evaluated using bright-field histochemical microscopy. Lactate dehydrogenase showed significant reactivity which increased with vessel diameter in cortical and ganglionic vessels in all age groups tested. Succinate dehydrogenase and cytochrome oxidase showed little reactivity in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…the larger arterioles demon strate moderate to strong reactivity for this enzyme. Like the midbrain arterioles presently described in the mouse, Rieke and Cannon [ 1985] and Cannon et al [ 1985] demon strated that arterioles of the rat caudate nucleus were also capable of utilizing aerobic and anaerobic pathways.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…the larger arterioles demon strate moderate to strong reactivity for this enzyme. Like the midbrain arterioles presently described in the mouse, Rieke and Cannon [ 1985] and Cannon et al [ 1985] demon strated that arterioles of the rat caudate nucleus were also capable of utilizing aerobic and anaerobic pathways.…”
Section: Discussionmentioning
confidence: 66%
“…some his tochemical studies on arteriolar reactivity in the central nervous system have been reported [Cannon and Gelderd. 1983: Rieke and Cannon. 1985: Can non et al.…”
Section: Introductionmentioning
confidence: 99%
“…Smooth muscle in small arterioles is the key element for maintenance of vascular tone and the lumenal diameter (Milnor, 1974) and therefore for the regulation of blood flow through the arteriole (Edvinsson et al, 1979). Rieke and Cannon (1985) have shown that as ganglionic arteries (penetrating muscular arterioles) age there is a significant decrease in the availability of myosin ATPase in the muscular wall. The loss of ATPase may lead to a reduction in muscle tone and an increase in vessel diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the lowviscosity methyl methacrylate monomer perfused through the left heart or the aortic arch produces an accurate replica of the arterial vascular supply and the capillary bed of diverse vascular trees (Rieke et al, 1981;Hossler and Olson, 1984). The pattern of the arterial supply to the thalamus in the rat has not been defined, yet such a definition would seem essential for use of the rat as a model to study structural and metabolic changes related to aging and the mechanisms underlying stroke in humans (Rieke and Cannon, 1985). The relevance of defining the rat model for the thalamic arterial supply lies in the fact that the thalamus is a frequent site of hemorrhagic strokes in man (approximately 10-15%, Kase and Mohr, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…External vessel diameters were determined directly from photographic prints and by utilization of an eye-piece micrometer. Vessels with diameters less than 80 pm were considered microvessels (arterioles) [ 14,15]. Using the Leitz photometer DADS, described below, for each histochemical reaction, approximately 200 arterioles from each animal were examined and were photographed at the same light inten sity.…”
Section: Methodsmentioning
confidence: 99%